Collective entrepreneurship in the contemporary European services industries : a long term approach - Fernández Pérez, Paloma; San Román, Elena (Frontiers of management history., 2023)
Collective entrepreneurship plays an important role in European service activities such as tourism, health care, leisure, trade, logistics and transportation. Collective Entrepreneurship in the Contemporary European Services Industries provides a historical account and a managerial approach on how companies in the service industry have grown, innovated, and internationalised along the last centuries in Western Europe. Using collective entrepreneurship and collaborative networks within firms and between firms and external associations and institutions such as governments, the authors contribute to a better interdisciplinary understanding of the long-term dynamics of European companies. Collective Entrepreneurship in the Contemporary European Services Industries borrows and applies existing concepts and theories from business history and from entrepreneurship. A multidisciplinary and inter-territorial approach, this collection combines business history and entrepreneurship theory to respond to recent calls for a historic turn in entrepreneurship studies, offering the opportunity to relaunch the dialogue between history and theory.